Features of the distribution of the obesity phenotype depending on age - Ablaikhanova, N.T.; Okhas, I.M.; Tolebayeva, Z.K.; Yessenbekova, А.Е.; Mukhitdin, B.A.; Ussipbek, B.A.; Duisenbek, A.A.; Kozhamzharova, L.S. (Karagandy University of the name of acad. E.A. Buketov, 2025)
The article analyzes the prevalence of the metabolically healthy obesity (MHO) phenotype concerning age and gender. Similar to global studies, the criteria for this phenotype are actively being investigated in Kazakhstan. In 2017, the Kazakhstan Cardiology Center (KCC) presented a draft of recommendations regarding obesity. A key question revolves around the feasibility of classifying patients with metabolically healthy obesity phenotypes. It has been suggested that phenotype should be defined for each body mass index (BMI) group based on the waist-to-hip ratio. The findings indicate that the frequency of metabolic syndrome varies significantly depending on the classification used. Among women, metabolically healthy obesity phenotype occurs more frequently than in men, though its prevalence decreases with age. Individuals with metabolic syndrome, an increase in mean arterial pressure while maintaining normal levels of cholesterol, triglycerides, and high-density lipoproteins, regardless of the classification used. When using the KCC criteria to define MHO, the frequency of cardiometabolic risk factors was higher compared to other criteria. The conducted study revealed variability in the frequency of metabolic syndrome depending on the criteria used for classification: International Diabetes Federation (IDF) (2021) — 23.2 %, KCC (2021) — 27.1 %, NCEP ATP III (2021) — 41.8 %. Depending on age, the frequency of MHO phenotype in menopausal women showed a statistically significant increase across all classifications. A notable decline in the prevalence of is observed in statistical indicators among women over the age of 55.
Keywords: obesity; metabolically healthy obesity phenotype; metabolism; age and gender characteristics; arterial hypertension; diabetes mellitus